2011
DOI: 10.1007/s13187-010-0189-4
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cancer Knowledge: A Survey Administered to Patients in Dental Departments at Large Italian Hospitals

Abstract: We assessed the oral cancer (OC) knowledge, including risk factors and clinical symptoms, among patients attending dental departments within Italian university hospitals. Two thousand and two hundred questionnaires were sent to four hospitals in order to assess patients’ knowledge regarding clinical and epidemiological aspects of OC; OC knowledge was evaluated overall and stratified by oral cancer family history. Participants frequently identified cigarette smoking (87.8%) and heavy alcohol consumption (58.6%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 21 publications
7
25
1
3
Order By: Relevance
“…In the present study, the knowledge regarding risk factors was rather poor; although around two thirds of the subjects identified tobacco use as a risk factor, only 56 % knew that alcohol consumption is also a potential risk factor. These findings are in line with most studies, which found greater public awareness of tobacco as a risk factor compared with alcohol consumption [16,19,[21][22][23]28]. The greater awareness of tobacco as a risk factor could be attributed to anti-tobacco media campaigns explaining the adverse effects of smoking.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, the knowledge regarding risk factors was rather poor; although around two thirds of the subjects identified tobacco use as a risk factor, only 56 % knew that alcohol consumption is also a potential risk factor. These findings are in line with most studies, which found greater public awareness of tobacco as a risk factor compared with alcohol consumption [16,19,[21][22][23]28]. The greater awareness of tobacco as a risk factor could be attributed to anti-tobacco media campaigns explaining the adverse effects of smoking.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, around one third of Saudi subjects were tobacco smokers, and, surprisingly, although the majority of smokers (62.3 %) knew that smoking was a risk factor for oral cancer, they continued to smoke. Similarly, majority of smoking adults from Italy [28] and more than half of smoking adults from Kuwait [29] were aware of the correlation between heavy smoking and oral cancer but, nevertheless, continued to smoke. Patients knew that smoking and heavy alcohol consumption were risk factors for oral cancer but did not change behavior.…”
Section: Discussionmentioning
confidence: 99%
“…However, more alarming was the observation that only quarter of the study population got information about oral cancer from a dentist, emphasising the need on the part of dental professionals to inform and educate their patients better about oral cancer. This finding is similar to the study by Villa et al (2011) done on Italian dental patients, where less than 15% reported having received oral cancer counselling by a dentist or a physician. Also, this study stated that only 1.6% were aware of their oral cancer examination which could be because of their high-risk behaviour pattern.…”
Section: Discussionsupporting
confidence: 90%
“…The study methods have been described previously [15]. Briefly, questionnaires were sent to the dental departments of four Italian university hospitals (550 per hospital): University of Messina, Umberto I Hospital; University La Sapienza, San Paolo Hospital; University of Milano, and San Raffaele Hospital, University Vita e Salute.…”
Section: Methodsmentioning
confidence: 99%